Arctic Coralline Algae Elevate Surface pH and Carbonate in the Dark - Hofmann, Laurie C.; Schoenrock, Kathryn; de Beer, Dirk (Frontiers in Plant Science, 2018)
Red coralline algae are projected to be sensitive to ocean acidification, particularly in polar oceans. As important ecosystem engineers, their potential sensitivity has broad implications, and understanding their carbon acquisition mechanisms is necessary for making reliable predictions. Therefore we investigated the localized carbonate chemistry at the surface of Arctic coralline algae using microsensors. We report for the first time carbonate ion concentration and pH measurements ([CO32-]) at and above the algal surface in the microenvironment. We show that surface pH and [CO32-] are higher than the bulk seawater in the light, and even after hours of darkness. We further show that three species of Arctic coralline algae have efficient carbon concentrating mechanisms including direct bicarbonate uptake and indirect bicarbonate use via a carbonic anhydrase enzyme. Our results suggest that Arctic corallines have strong biological control over their surface chemistry, where active calcification occurs, and that net dissolution in the dark does not occur. We suggest that the elevated pH and [CO32-] in the dark could be explained by a high rate of light independent carbon fixation that reduces respiratory CO2 release. This mechanism could provide a potential adaptation to ocean acidification in Arctic coralline algae, which has important implications for future Arctic marine ecosystems.